Quantitative glucose detection by surface-enhanced Raman spectroscopy using viologens as reporter. - Cheng, Chun Chieh. (2010)
This research presents the study towards a glucose biosensor using surface-enhanced Raman scattering (SERS) spectroscopy with benzyl viologen boronic acid (BVB1). According to previous studies, glucose has been difficult to detect by SERS due to its poor Raman cross section and its inability to absorb onto metallic surfaces. In this report, the study of indirect glucose detection via SERS is documented. Previous studies have shown the affinity of boronic acid towards monosaccharides. By incorporating the usage of Au substrates and a monolayer of BVB1, glucose molecules are captured by the boronic acid groups of BVB1, inducing conformation and orientation changes. Analysis of the SERS data collected suggests that glucose could be quantitatively detected in the physiological concentration range, with a linear predictive capability. The results obtained also fall within the acceptable regions of the Clarke error grid (Region A and B). The root-mean-square error of calibration (RMSEC) is approximately 41.24 mg/dl (2.29 mM) which is comparable to other studies. Data collected on the surface modification of silver/gold (bimetallic) film over nanospheres (FON) also demonstrated the theoretical mechanism of glucose sensing proposed by the group. Future works would include optimizing the sensing system by covalently binding BVB1 with the Au surface as well as using fiber optics, to produce a real time, in vivo glucose monitoring option that is minimally invasive.